Modified fibrinolytic therapy as treatment of mechanical aortic valve thrombosis. (March 2021) - Mustafa, Ala; Thomas, Todd; Murdock, Robert; Congello, Samuel
Prosthetic valve thrombosis is a rare phenomenon with limited treatment options. Current management choices include anticoagulation with or without fibrinolysis or surgical valve replacement for appropriate candidates. We report an alternative fibrinolytic and anticoagulation regimen resulting in successful treatment of a patient presenting with mechanical aortic valve thrombosis.